Translational and clinical comparison of whole genome and transcriptome to panel sequencing in precision oncology - Kerle, Irina Anja; Gross, Thomas; Kögler, Anja; Arnold, Jonas S.; Werner, Maximilian; Eckardt, Jan-Niklas; Möhrmann, Elena E.; Arlt, Marie; Hutter, Barbara; Hüllein, Jennifer; Richter, Daniela; Schneider, Martin M. K.; et al. (npj precision oncology, 2025)
Precision oncology offers new cancer treatment options, yet sequencing methods vary in type and scope. In this study, we compared whole-exome/whole-genome (WES/WGS) and transcriptome sequencing (TS) with broad panel sequencing by resequencing the same tumor DNA and RNA as well as normal tissue DNA for germline assessment, from 20 patients with rare or advanced tumors, who were originally sequenced by WES/WGS ± TS within the DKFZ/NCT/DKTK MASTER program from 2015 to 2020. Molecular analyses resulted in a median number of 2.5 (gene panel) to 3.5 (WES/WGS ± TS) treatment recommendations per patient. Our results showed that approximately half of the therapy recommendations (TRs) of both sequencing programs were identical, while approximately one-third of the TRs in WES/WGS ± TS relied on biomarkers not covered by the panel. Eight of 10 molecularly informed therapy implementations were supported by the panel, the remaining two were based on biomarkers absent from the panel, highlighting the potential additional clinical benefit of WGS and TS.